Digital Public Mental Health: a dataset for monitoring mental health in Brazil - Gabriel Souto; Marcel Pedroso; Raquel de Souza Martins; Rebecca Salles; Matheus Miloski; Carmen Corrêa Bonifácio; Ariane Camilo Pinheiro Alves; Carlos Leonardo Souza Cardoso; Carolina C. Carvalho; Ricardo A. D. Oliveira; Flavio Kapczinski; Ives C. Passos; et al. (Scientific Data, 2026)
Abstract The scarcity of primary data and challenges in analyzing secondary data hinder comprehensive mental health monitoring and the development of evidence-based policies. In Brazil, although multiple health information systems capture critical mental health data, these systems lack integration, robust analysis, and systematic presentation of mental health indicators. This study introduces the Digital Public Mental Health Dataset, a comprehensive, transparent, and reproducible data resource that consolidates data from existing Brazilian health information systems. This dataset enables detailed tracking of mental health indicators, supports future research, and informs public health interventions to address mental health disparities.